Borehole closure at Mizuno Station, Antarctica - Kawada, Kunio; Yoshida, Minoru; Naruse, Renji (1986)
P(論文) The 400-m deep hole drilled in 1983 at Mizuho Station, East Antarctica, was used for measurements of the contraction of diameter in 1984. Depth-profiles of the diameter were obtained several times by using a three-contact-points caliper. Relationship between the stress and the strain rate of ice in the borehole was evaluated under the assumption that the strain rate was constant in the early stage of strain below approximately 0.08. Closure rates of the hole at Mizuho Station showed almost the same values as or slightly higher values than those in the same stress range derived by W. S. B. PATERSON (Rev. Geophys. Space Phys., 15,47,1977) in Antarctica and other ice caps. departmental bulletin paper